DOI: 10.11606/d.11.2018.tde-20181127-161527
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da disponibilidade de fósforo por diversos extratores em solos cultivados com cana-de-açúcar (<i>saccharum spp</i>)

Abstract: 2.3.1. Classif'icação dos méLodos para dosagem de fósforo 2.3.2. Escol ha de métodos-cr i t-ér i os e comparações. .. .. .. .. .. . 2.3.3. Histórico da cultura da cana-de-açócar em relação aos extrat-ores de fósforo do solo, no Brasil 2.4. Comentários sobre os trabalhos revisados

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
6

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
6
0
6
Order By: Relevance
“…Different studies have shown that Mehlich-1 extracted Ca-P (in greater proportion) along with some Fe-P and Al-P forms while Bray-1 extracted Al-P (in greater proportion) and Fe-P (Nováis and Smyth, 1999). Due to this differential extraction, where large amounts of Ca-P exist following application of rock phosphate (RP), the anion-resin will be more effective at estimating available-P (Braga et al, 1991 ;Silva and Raij, 1996), while among the acid extractors, Bray-1 would be the most satisfactory (Kamprath and Watson, 1980;Bahia Filho et al, 1982;Fixen and Grove, 1990). …”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that Mehlich-1 extracted Ca-P (in greater proportion) along with some Fe-P and Al-P forms while Bray-1 extracted Al-P (in greater proportion) and Fe-P (Nováis and Smyth, 1999). Due to this differential extraction, where large amounts of Ca-P exist following application of rock phosphate (RP), the anion-resin will be more effective at estimating available-P (Braga et al, 1991 ;Silva and Raij, 1996), while among the acid extractors, Bray-1 would be the most satisfactory (Kamprath and Watson, 1980;Bahia Filho et al, 1982;Fixen and Grove, 1990). …”
Section: Introductionmentioning
confidence: 99%
“…1994Fotvma et al, 1996Guo etal., 1996Manila, 1996Silva and Raij, 19% Simonis and Setatou, 1996aSimonis and Setatou., 1996b New The Pi and the resin methods have similarities and the comparisons than can be made with the data of Table 1 indicate that both present higher values of the percent variation as compared to the Olsen method. The Pi method presented a higher value than the resin in the paper of Menon et al (1988), equivalent or slightly lower in the data of Kumar et al (1992) and lower for the data of Silva and Raij (1996).…”
Section: Referencementioning
confidence: 70%
“…Esse método, mediante uma mistura de resinas de troca aniônica e catiônica, permite também a extração de outros nutrientes, como Ca, Mg e K (Raij et al, 1986). Silva & Raij (1996) e Büll et al (1998) demonstraram boa capacidade desse método de predição da disponibilidade de P do solo para diversas culturas. Silva & Raij (1999), em estudo comparativo de métodos, englobando a revisão de 72 trabalhos, concluíram que a resina trocadora de íons foi superior aos demais na correlação entre o P absorvido pelas plantas e o P extraído do solo.…”
Section: Introductionunclassified